Geological characteristics and development effect evaluation of coalbed methane reservoirs in Panguan syncline, Guizhou Province - Haiyang HU; Fuqin YANG; Jie CHEN; Yi LOU; Yuting WAN (Shiyou shiyan dizhi)
The Upper Permian Longtan Formation in Guizhou Province contains multiple coal seams with abundant coalbed methane (CBM) resources, providing a solid base for CBM development. However, the low permeability of the coal seams hinders gas and water production, necessitating the development of key technologies for CBM development under conditions of low permeability and multiple coal seams in Guizhou. Based on the geological characteristics of coal reservoirs in the Panguan syncline and CBM well engineering data, the study analyzed geological, fracturing, and drainage and production parameters, and summarized development technologies for low-permeability and multi-seam CBM reservoirs. Engineering practices in Panguan syncline show that: (1) For commingled development of coal seams 12# and 18# in the syncline, factors such as permeability, reservoir temperature, fracture pressure, liquid and sand addition per meter of coal seam, pressure drop rate, and production enhancement rate significantly influence gas production of CBM wells. (2) Increasing the liquid and sand addition per meter of coal seam can significantly increase the reservoir permeability after fracturing. The permeability of well YP-1 after fracturing reached 64.158×10-3 μm2, 1 304 times higher than before. (3) Controlling pressure drop rate and production enhancement rate to appropriate levels can improve the fracturing fluid flowback rate and expand the pressure drop funnel radius of CBM wells. The cumulative fracturing fluid flowback rate of well YP-1 reached 82.53% after 210 days of drainage and production, with the water production radius reaching 91% of the fracturing influence radius. This helps to expand effective desorption radius and improve the effectiveness of gas production. For the Panguan syncline with low permeability and multiple coal seams, the study suggests adopting the technical approach of "selected layer perforation, segmented fracturing, and commingled drainage and production" to improve the geological and engineering potential of CBM development.